2020
DOI: 10.1038/s41386-020-00798-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antibiotic use during early life and risks to mental traits: an observational study and gene–environment-wide interaction study in UK Biobank cohort

Abstract: The relationships between long-term antibiotic use during early life and mental traits remain elusive now. A total of 158,444 subjects from UK Biobank were used in this study. Linear regression analyses were first conducted to assess the correlations between long-term antibiotic use during early life and mental traits. Gene-environment-wide interaction study (GEWIS) was then performed by PLINK2.0 to detect the interaction effects between long-term antibiotic use during early life and genes on the risks of ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…In particular, prenatal or early life antibiotic exposure is associated with an increased risk for psychiatric disorders [32], which is consistent in the experimental animal model of microbiota depletion by chronic postweaning exposure to antibiotics [32]. At the molecular levels, human population-based assessment of gene-environment interaction indicated the positive associations of early-life long-term exposure to antibiotics with the expression of genes involved in anxiety and depression [33]. Moreover, antibiotic-induced behavioral alterations have been extensively evaluated in association with neuroendocrine regulation in diverse experimental models [34][35][36].…”
Section: Introductionsupporting
confidence: 67%
“…In particular, prenatal or early life antibiotic exposure is associated with an increased risk for psychiatric disorders [32], which is consistent in the experimental animal model of microbiota depletion by chronic postweaning exposure to antibiotics [32]. At the molecular levels, human population-based assessment of gene-environment interaction indicated the positive associations of early-life long-term exposure to antibiotics with the expression of genes involved in anxiety and depression [33]. Moreover, antibiotic-induced behavioral alterations have been extensively evaluated in association with neuroendocrine regulation in diverse experimental models [34][35][36].…”
Section: Introductionsupporting
confidence: 67%
“…Associations between antibiotic exposure and psychiatric disorders have been found in multiple large population-based studies (Köhler et al, 2017;Liang et al, 2021;Lurie, Yang, Hayne, Mamtani, & Boursi, 2015). Lurie et al (2015) found that treatment with a single antibiotic course was associated with higher risk for depression (n = 202,974) compared to a healthy control group (n = 803,961), with adjusted ORs of 1.23 [95% confidence level (CL) 1.18-1.29] for penicillin's and 1.25 (95% CL 1.15-1.35) for quinolones.…”
Section: Gut Microbiomementioning
confidence: 99%
“…However, Lurie et al ( 2015 ) did not find an association between antibiotic use and psychosis ( n = 8487). Liang et al ( 2021 ) observed positive associations between long-term antibiotic use during early life (defined by the UK Biobank as child or teenager) and anxiety and depression. Lastly, there are also studies showing that antibiotic use can induce hypomania or mania, also known as antibiomania (Abouesh, Stone, & Hobbs, 2002 ).…”
Section: Gut Microbiomementioning
confidence: 99%
“…Pathogenic bacteria with devastating consequences to human health have been studied extensively for more than 100 years, which induces symptoms ranging from mild to severe and can even result in death. , Antibiotics, including penicillin, which was first discovered in 1928, have been widely used to treat ailments caused by bacteria . However, some drug-resistant bacteria are produced due to the long-term abuse of antibiotics by humans, which seriously threatens human health. For example, the World Health Organization has reported a type of methicillin-resistant Staphylococcus aureus ( S. aureus ), a set of Gram-positive strains, that has developed resistance to some antibiotics and has become the primary source of some common infectious diseases . Currently, we are in a dilemma where the production of certain functional antibiotics is neck and neck with the development of drug-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%